ENVIRONMENTAL INVESTMENTS IN THE MINING INDUSTRY: THE NATURE, CHARACTERISTICS AND TYPES - N. Goncharenko; V. Korotkiy (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Theoretical basis for environmental investment enterprises in the mining industry was investigated. The essence of the category “environmental investments” was improved. The features to attract environmental investment in the mining sector were analyzed, their classification by expanding classifications were improved. The essence and characteristics of natural, industrial and human capital as an object of environmental investment of mining industry were determined.